Gambaran Prevalensi Stunting di Lokus dan Non-Lokus Stunting di Kota Bogor Tahun 2021-2023 - Nento, Putri Rahmawati; Aries, Muhammad (Jurnal Ilmu Gizi dan Dietetik, 2024)
Stunting has a detrimental effect on the development of the next generation of Indonesians and currently, it is still a serious health concern in Indonesia. One of the ways the stunting intervention program is implemented holistically up to the village/subdistrict level is by designating a place that is focused on stunting (lokus). The purpose of this study is to examine trends in stunting instances at both stunting lokus and non-lokus in Bogor City. The study used descriptive analysis models with secondary data from the 2021–2023 results of the Health Office about child under 59 months old body height/length database. The study's findings indicated that the prevalence of stunting has declined in 61 subdistricts, which are distributed across 8 locus subdistricts with an average decrease of 5.74% and 53 non-locus subdistricts with an average decreased of 3.81%. Meanwhile, the prevalence has increase in 7 non-locus subdistricts with an average increase of 1.12%.